2019
DOI: 10.1186/s11658-019-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of different SIRT1-mediated signaling pathways in toxic injury

Abstract: Common environmental pollutants and drugs encountered in everyday life can cause toxic damage to the body through oxidative stress, inflammatory stimulation, induction of apoptosis, and inhibition of energy metabolism. Silent information regulator 1 (SIRT1), a nicotinamide adenine dinucleotide-dependent deacetylase, is a member of the evolutionarily highly conserved Sir2 (silent information regulator 2) superprotein family, which is located in the nucleus and cytoplasm. It can deacetylate protein substrates in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 77 publications
1
89
0
Order By: Relevance
“…Activated SIRT1 deacetylates and affects the activity of both members of the peroxisome proliferator-activated receptor gamma coactivator 1-alpha/estrogen-related receptor alpha (PGC1α/ERRα) complex and FOXO1/3, which are essential metabolism regulatory transcription factors [162,163]. SIRT1 uses first pathway, PGC1α/ERRα, so as to induce nuclear factor erythroid 2-related factor 2 (Nrf2), yet, it is also capable of direct activation of Nrf2 using numerous mechanisms [164]. The latter negatively impacts on proinflammatory cytokines (e.g., TNF-α, IL-1) and acts as a master regulator of mitochondrial biogenesis and transcription of genes possesing ARE (antioxidant response elements) (e.g., CAT, GPx, heme oxygenenase (HO-1), SOD1/2, GSH, peroxiredoxin 3/5 (PRDX3/5), thioredoxin-interacting protein (TXNIP), NAD(P)H-quinone oxidoreductase 1 (NQO1), glutathione S-transferases (GSTs), glutamate-cysteine ligase modifier subunit (GCLM), cysteine ligase catalytic subunit (GCLC), glucose-6-phosphate dehydrogenase (G6PD)) [164][165][166][167].…”
Section: Mirnas In Mets-a Link With Obesity and Insulin Resistance/hymentioning
confidence: 99%
“…Activated SIRT1 deacetylates and affects the activity of both members of the peroxisome proliferator-activated receptor gamma coactivator 1-alpha/estrogen-related receptor alpha (PGC1α/ERRα) complex and FOXO1/3, which are essential metabolism regulatory transcription factors [162,163]. SIRT1 uses first pathway, PGC1α/ERRα, so as to induce nuclear factor erythroid 2-related factor 2 (Nrf2), yet, it is also capable of direct activation of Nrf2 using numerous mechanisms [164]. The latter negatively impacts on proinflammatory cytokines (e.g., TNF-α, IL-1) and acts as a master regulator of mitochondrial biogenesis and transcription of genes possesing ARE (antioxidant response elements) (e.g., CAT, GPx, heme oxygenenase (HO-1), SOD1/2, GSH, peroxiredoxin 3/5 (PRDX3/5), thioredoxin-interacting protein (TXNIP), NAD(P)H-quinone oxidoreductase 1 (NQO1), glutathione S-transferases (GSTs), glutamate-cysteine ligase modifier subunit (GCLM), cysteine ligase catalytic subunit (GCLC), glucose-6-phosphate dehydrogenase (G6PD)) [164][165][166][167].…”
Section: Mirnas In Mets-a Link With Obesity and Insulin Resistance/hymentioning
confidence: 99%
“…Studies have shown ( 29 ) that miR-4534 is overexpressed in prostate cancer (PCA) and blocks cell proliferation, migration, induce G0/G1 cell cycle arrest and apoptosis, thus affecting tumor tissue growth, which may provide a therapeutic target and mechanism for the treatment of PCA in the future. In order to further explore the pathogenesis of DKD, our research group obtained a KEGG pathway map of miR-4534 through bioinformatics analysis ( Figure 8 ), of which SIRT1/FOXO signaling pathway ( 30 ) is most closely related to DKD. It is well-known that studies on the pathogenesis of DKD are increasingly focused on inflammatory responses ( 31 ), and FOXO is one of the most well-known pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate genetic susceptibility is likely to play a role in response to air pollution, especially on cardiovascular and respiratory outcomes [30]. A recent review indicated that SIRT1 plays in toxicological damage caused by environmental toxicants such as PM 2.5 , the PM-induced injury affects SIRT1 expression, which then affects the expression and activity of downstream proteins, resulting in toxic damage [42]. In addition, one molecular biology nding suggested that PM 2.5 can upregulate MicroRNA-146a-3p and induces the in ammatory macrophage polarization by targeting SIRT1 [43].…”
Section: Discussionmentioning
confidence: 99%